2017
DOI: 10.1042/cs20170220
|View full text |Cite
|
Sign up to set email alerts
|

A past and present overview of macrophage metabolism and functional outcomes

Abstract: In 1986 and 1987, Philip Newsholme et al. reported macrophages utilize glutamine, as well as glucose, at high rates. These authors measured key enzyme activities and consumption and production levels of metabolites in incubated or cultured macrophages isolated from the mouse or rat intraperitoneal cavity. Metabolic pathways essential for macrophage function were then determined. Macrophages utilize glucose to generate (i) ATP in the pathways of glycolysis and mitochondrial oxidative phosphorylation, (ii) glyce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
64
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(68 citation statements)
references
References 91 publications
0
64
0
Order By: Relevance
“…In addition to fatty acid oxidation and glycolysis, oxidative phosphorylation can be fueled by glutamine, the most abundant circulating amino acid in mammals and a major TCA substrate via its catabolism to α-ketoglutarate (αKG) (Newsholme et al 1986;Fan et al 2013;Curi et al 2017). We found that, unlike control macrophages, MPKO macrophages were unable to effectively respire using glutamine as fuel (Fig.…”
Section: Pparγ Is Required For Respiration From Glutaminementioning
confidence: 92%
“…In addition to fatty acid oxidation and glycolysis, oxidative phosphorylation can be fueled by glutamine, the most abundant circulating amino acid in mammals and a major TCA substrate via its catabolism to α-ketoglutarate (αKG) (Newsholme et al 1986;Fan et al 2013;Curi et al 2017). We found that, unlike control macrophages, MPKO macrophages were unable to effectively respire using glutamine as fuel (Fig.…”
Section: Pparγ Is Required For Respiration From Glutaminementioning
confidence: 92%
“…Monocytes bind to activated endothelium, migrate into the intimal layer and take up lipoproteins to become macrophages. Monocyte/macrophages can induce the release of inflammatory factors, promote AS formation and induce plaque rupture, leading to the occurrence of acute coronary syndrome (ACS) 9,[12][13][14][15] . Previous study showed that monocytes are functionally different in hyperlipidemia 16 .…”
Section: Discussionmentioning
confidence: 99%
“…Macrophages depend to varying degrees upon glutamine, glucose and fatty acids as fuels [136] and glutamine is an important immune regulator [137]. 14 different solute carriers from 4 families have been shown to transport glutamine [138].…”
Section: Expression Of Solute Carriers and Metabolism Genes In Macropmentioning
confidence: 99%